1980
DOI: 10.1046/j.1537-2995.1980.20581034503.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Criteria for Blood Donor Deferral

Abstract: Donor deferral rates in regional blood centers vary from 5 to 24 per cent, reducing by more than 1,250,000 the number of units of volunteer blood available for transfusion in the nation each year. Those criteria for donor deferral which are intended to exclude donors likely to suffer a "donor reaction" are based partially on untested hypotheses and tradition. In a six-month prospective study, we adopted more liberal criteria for donor acceptance. During this period, donor reaction rates did not increase, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
83
1
2

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 14 publications
10
83
1
2
Order By: Relevance
“…Donor deferral rates in blood canters vary from 5 to 24% leading to huge losses in terms of available units for transfusion in the nation every year. [6] In the present study the overall deferred rate was 4.27% and the deferred rate was higher in males (65.33%) compared to females (34.67%).This was similar to that observed by Unikrishnan B [1] (5.2%), Sundar P [3] (6%), Agnihothri N [5] (11.6%). The higher rate (8-15%) was reported by Chaudhary [7] , Lim [2] , Blumberg [8] , Ranveet.…”
Section: Discussionsupporting
confidence: 89%
“…Donor deferral rates in blood canters vary from 5 to 24% leading to huge losses in terms of available units for transfusion in the nation every year. [6] In the present study the overall deferred rate was 4.27% and the deferred rate was higher in males (65.33%) compared to females (34.67%).This was similar to that observed by Unikrishnan B [1] (5.2%), Sundar P [3] (6%), Agnihothri N [5] (11.6%). The higher rate (8-15%) was reported by Chaudhary [7] , Lim [2] , Blumberg [8] , Ranveet.…”
Section: Discussionsupporting
confidence: 89%
“…In our study Female donors had a statistically significant higher rate of VVR, which supports findings of previous studies [13][14][15] . On the other hand many other authors reported that there is no significant difference between men and women donors for VVR [16][17][18] . We found that 71.2% of donors suffered with VVR were new donor and 28.8% were repeat donor.…”
Section: Discussionmentioning
confidence: 87%
“…Varios autores coinciden en que la edad menor de Diversos factores relacionados con la experiencia 25 a 30 años y la donación por primera vez son de la donación influyen en el retorno de donantes a factores de riesgo para la presencia de efectos indeseables a la donación (1,2,(6)(7)(8). Esta situación podría explicarse porque usualmente la primera donación se efectúa a más temprana edad; además, las personas jóvenes tienen sensibilidad barorreceptora ventncular más baja que los individuos mayores, quienes suelen ser hemodinámicamente más estables (1).…”
Section: Resultsunclassified
“…El sexo femenino fue un factor de predisposición a la reacción vasovagal, a diferencia de lo registrado en otros estudios (1,6,7). Una posible explicación puede ser el peso corporal menor en el sexo femenino con relación al sexo masculino (cuadro l), con la consiguiente hipovolemia, secundaria al mayorvolumen de sangre perdido, en donantes de más baja estatura.…”
Section: Resultsunclassified